PELAKSANAAN ITSBAT NIKAH DI PENGADILAN AGAMA PADANG KELAS 1 A - Irma Irawati dan Joni Zulhendra (Fakultas Hukum Universitas Tamansiswa Padang, 2019)
The family is one of the smallest social units in society, the formation of a family is the existence of a strict bond between a woman and a man that is carried out in marriage.